Lameness in cattle: recent research to inform clinical practice - Maxwell, O.J.R.; Miguel-Pacheco, G.G.; Newsome, R.; Randall, L.V.; Remnant, J.G.; Thomas, H.J.; Huxley, J.N. (BMJ Publishing Group, 2015)
Lameness in cattle has significant consequences for welfare, health and productivity. More research is now being done on lameness and this article, the first in a two-part series, provides an update on research-based advances in the field published from around the world over the past five years. These developments have improved our understanding of lameness in cattle and can inform clinical practice and the control of lameness on-farm. The second article, to be published in a subsequent issue of In Practice, will cover the understanding and management of claw health and claw horn lesions.